Nilai Pendidikan Islam Pada Masyarakat Jawa-Mabar - Siti Khoirul Bariyah; Nur Rizki; Nadira Ulfa Hasibuan (Kitabah: Jurnal Pendidikan Sosial Humaniora, 2023)
Writing this article aims to find out more deeply about the values of Islamic education that exist in Javanese society in the Mabar Hilir area, Medan. The research method used in writing this article is a qualitative method. The results of the study can be described that the values of Islamic education in the Javanese community in the Mabar Hilir area are heavily influenced by ancestral culture. As we know that the Javanese adhere to many Hindu-Buddhist values, animism and dynamism when Islam entered the Java region, therefore the majority of Javanese people still follow Hindu-Buddhist traditions and customs, animism and dynamism.